High school students' mathematic literacy performance in solving linear programming problem - Sugiarto, Iwan Jadi; Usodo, B; Saputro, D R S (Journal of physics. Conference series, 2021)
The mathematic literacy performance is the capability that is gotten by students applied on daily activities. The ability which uses logical thinking and knowledge that they got can solve the proses of learning till the subject can be used for life in 21 centuries. This research supposes to describe mathematic ability of student on grade XI IPA 1 SMA N 1 Karangdowo. This type of research is qualitatively descriptive. The research subject of 32 students which are taken using purposive sampling method. The result of research shows that mathematic literacy performance of student only reach on the third level, those are can present the resource information. The first indicator is 87,50% which the highest categorized. The second indicator is 75,78% which the higher categorized. The third indicator is 70,31% which the medium categorized. The fourth indicator is 39,06% which the low categorized. The fifth indicator is 1,56% which the lower categorized and on the sixth indicator is 0%, so that overall can be seen the average mathematic literacy performance for student grade XI IPA 1 is 45,70% with low categorized. The teacher should not push comprehension routine procedural but also variety in giving problem.